ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN PADA PT WASKITA KARYA (PERSERO) TBK PERIODE 2018-2022 - Fina Pandu Winata Gee (Jurnal Ilmiah Mahasiswa Nias Selatan, 2025)
The purpose of this study was to determine the clarity of the company's financial performance based on the analysis of liquidity ratios and profitability ratios at PT WaskitaKarya (Persero) Tbk in 2018-2022. The type of research used is qualitative research with a descriptive approach, while the data source is the audited published financial statements from 2018 to 2020. The data analysis method used is liquidity ratio analysis and profitability analysis. The results of this study indicate that the assessment of the financial performance of PT WaskitaKarya (Persero) Tbk, based on the liquidity ratio measured by the current ratio from 2018-2022 is in a fairly good condition. The financial performance of PT WaskitaKarya (Persero) Tbk then measured based on the fast ratio in 2018-2022 the assessment criteria are said to be quite good. The financial performance of PT WaskitaKarya (Persero) Tbk is then measured based on the cash ratio in 2018-2022 the assessment criteria are said to be less good. Assessment of the financial performance of PT WaskitaKarya (Persero) Tbk, based on profitability ratios measured by net profit margin (npm) in 2020 then the assessment criteria are said to be quite good. The assessment of financial performance measured based on return on assets (roa) from 2018-2022 is in a bad condition, while the assessment of financial performance based on return on equity (roe) from 2018-2022 then the assessment criteria is said to be less good. Based on the results of this study, as a suggestion is to increase the company's profit financial performance of PT. WaskitaKarya (Persero) Tbk, it is better if current assets are needed to be increased than current debt owned by the company so that it can make the company's finances good. To improve the financial performance of the company PT. WaskitaKarya (Persero) Tbk, it is better if all the company's obligations need to be adjusted to the profit earned by the company so as to increase and maintain the company's ability to generate assets or assets.